Penafsiran Kontekstual Ulama Kontemporer Atas Ayat-Ayat Poligami - Aspandi Aspandi; Tiya Wardah Saniyatul Husnah (Saintifika Islamica, 2022)
Polygamy is a practice that is still often debated for a long time among scholars, mujtahids and the public. There are so many different interpretations of the polygamous verse but some people interpret the polygamy verse partially which eventually leads to a partial interpretation, in this study examining the verse with the contextual method of interpreting the verse as a whole from socio-historical and all other aspects. The author uses a literature review research methodology, a type of qualitative research that includes explanations of theories, results, and other research materials. Primary data sources are journals and books that discuss the interpretation of polygamy verses. From this research, the results found are the meaning of the polygamous verse as a whole from socio-historical and all other aspects, so that it can provide a deep understanding and can view the polygamous verse with the lens of justice, the recommended marriage model in Islam is monogamy, because monogamy is in accordance with Mawaddah, Rahmah, Sakinah and polygamy are allowed in very urgent circumstances.